THE COLOR OF CHOCOLATE PRODUCT PACKAGING AT INTEGRATED SERVICE UNIT SIKKA INNOVATION CENTER, SIKKA DISTRICT, EAST NUSA TENGGARA - Karrol, Yohanes Paulus; Iskandar, M Syahril (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Sikka chocolate (Cho-Sik), a chocolate product from Sikka District, is produced by the UPT Sikka Innovation Center. Packaging plays a crucial role as it attracts consumers, acting as a silent salesman. The choice of colors in packaging significantly influences consumer purchasing decisions. However, Cho-Sik, managed by the government, lacks adequate packaging design. This research aims to understand how color elements in Cho-Sik packaging affect consumer behavior. Using qualitative methods such as interviews, observations, and literature reviews, the study found that the packaging colors align with the chocolate variants produced. These findings offer insights into enhancing buyer interest and guiding marketers in utilizing colors effectively in Cho-Sik packaging design, catering to both domestic and international markets.